2022
DOI: 10.1093/nutrit/nuac013
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between breastfeeding and motor development in children: a systematic review and meta-analysis

Abstract: Context The importance and benefits of breastfeeding in children are well recognized, and it may improve motor development. Motor skills are fundamental to childhood development. Although some studies report a positive association between breastfeeding and motor development in children, others have suggested that these differences could be influenced by confounding variables. Objective To estimate the degree to which breastfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…The negative association between current breastfeeding and child development is contrary to reports from previous studies, where breastfeeding has been associated with better development, especially motor skills, with effect sizes ranging from 0.5 to 10.9 between breastfed versus nonbreastfed (Bernardo et al, 2013; Horta et al, 2015; Quinn et al, 2001; Sacker et al, 2006). However, the results of these studies are prone to confounding, and in adjusted analyses, the effect sizes between breastfed versus nonbreastfed tend to be attenuated: 0.4–8.2 (Bernardo et al, 2013; Hernández‐Luengo et al, 2022; Horta et al, 2007; Horta et al, 2015; Quinn et al, 2001; Sacker et al, 2006). In fact, Renee et al who studied the extent to which confounding explained the association between breastfeeding duration and cognitive development up to 14 years of age, reported that adjusting for SES tended to halve the effect sizes, while further adjustment for maternal cognitive scores explained the remaining association at 5 years of age, while there was still an effect at ages 7, 11 and 14 (Pereyra‐Elías et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The negative association between current breastfeeding and child development is contrary to reports from previous studies, where breastfeeding has been associated with better development, especially motor skills, with effect sizes ranging from 0.5 to 10.9 between breastfed versus nonbreastfed (Bernardo et al, 2013; Horta et al, 2015; Quinn et al, 2001; Sacker et al, 2006). However, the results of these studies are prone to confounding, and in adjusted analyses, the effect sizes between breastfed versus nonbreastfed tend to be attenuated: 0.4–8.2 (Bernardo et al, 2013; Hernández‐Luengo et al, 2022; Horta et al, 2007; Horta et al, 2015; Quinn et al, 2001; Sacker et al, 2006). In fact, Renee et al who studied the extent to which confounding explained the association between breastfeeding duration and cognitive development up to 14 years of age, reported that adjusting for SES tended to halve the effect sizes, while further adjustment for maternal cognitive scores explained the remaining association at 5 years of age, while there was still an effect at ages 7, 11 and 14 (Pereyra‐Elías et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Despite well-established physical, psychological, and social benefits of breastfeeding (Victora et al, 2016 ; Babic et al, 2020 ; Hernández-Luengo et al, 2022 ), exclusive breastfeeding for up to 6 months of an infant's age remained worldwide low (Neves et al, 2021 ). Even in more developed countries, such as the UK and the US, where initial breastfeeding rates were as high as 80%, the breastfeeding rate declined very fast, being 34% in the UK and 56% in the US for any breastfeeding rates and 1% in the UK and 25% in the US for rates of exclusive breastfeeding, at 6 months postpartum (UNICEF United Kingdom, 2022 ; US Centers for Disease Control Prevention, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that breastfeeding brings many health benefits to both mother [1,2] and infant. Acute benefits for infants include protection against neonatal morbidity and mortality [3] and against proinflammatory gastrointestinal conditions and infections [4,5], while long-term effects include reduced incidence of asthma [6] and (food) allergies, improved cardiometabolic health and reduced obesity risk [7][8][9], and improved neurocognitive functions [10,11]. Many aspects of breastfeeding may contribute to these health benefits.…”
Section: Introductionmentioning
confidence: 99%